2014
DOI: 10.1073/pnas.1412676111
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome-induced tuning of GTP hydrolysis by a translational GTPase

Abstract: GTP hydrolysis by elongation factor Tu (EF-Tu), a translational GTPase that delivers aminoacyl-tRNAs to the ribosome, plays a crucial role in decoding and translational fidelity. The basic reaction mechanism and the way the ribosome contributes to catalysis are a matter of debate. Here we use mutational analysis in combination with measurements of rate/pH profiles, kinetic solvent isotope effects, and ion dependence of GTP hydrolysis by EF-Tu off and on the ribosome to dissect the reaction mechanism. Our data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
69
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(92 citation statements)
references
References 63 publications
22
69
1
Order By: Relevance
“…3A). Consistent with previous observations (27), ribosomes are required to stimulate EF-Tu-mediated GTP hydrolysis, and virtually no hydrolysis of GTP was detected in their absence. EF-Tu hydrolyzed GTP in the presence of ribosomes in a time-dependent manner, and by 30 min ∼60% of the GTP was converted into GDP.…”
Section: Phosphorylation Of Ef-tu Inhibits Gtp Hydrolysis and Translasupporting
confidence: 92%
See 1 more Smart Citation
“…3A). Consistent with previous observations (27), ribosomes are required to stimulate EF-Tu-mediated GTP hydrolysis, and virtually no hydrolysis of GTP was detected in their absence. EF-Tu hydrolyzed GTP in the presence of ribosomes in a time-dependent manner, and by 30 min ∼60% of the GTP was converted into GDP.…”
Section: Phosphorylation Of Ef-tu Inhibits Gtp Hydrolysis and Translasupporting
confidence: 92%
“…EF-Tu hydrolyzed GTP in the presence of ribosomes in a time-dependent manner, and by 30 min ∼60% of the GTP was converted into GDP. The relatively modest levels of GTP hydrolysis observed likely are caused by the absence of mRNA and aa-tRNA in the reactions, which are required for full activation of EF-Tu GTPase activity (27). However, under the same conditions, GTP hydrolysis was reduced significantly in the presence of P∼EF-Tu to levels similar to those observed in the absence of ribosomes.…”
Section: Phosphorylation Of Ef-tu Inhibits Gtp Hydrolysis and Translamentioning
confidence: 81%
“…Nevertheless, the proposed general base mechanism continues to be intensively discussed and the role of the SRL, and the conserved histidine remains unclear (22,23). Recent studies favor a model where GTP hydrolysis is activated via substrate-assisted catalysis, thereby highlighting the importance of functional groups on the GTP substrate for the phosphoryl transfer mechanism (41,42). However, the contribution of the nonbridging phosphate oxygen at position 2662 of rRNA to GTP hydrolysis is still unclear.…”
Section: A2662 Thiophosphate Diastereomers Both Have Wt Activities Inmentioning
confidence: 99%
“…Very recently another residue, namely an aspartate residue (Asp21 of EF-Tu), has been shown to be crucial for stimulation of GTP hydrolysis by EF-Tu on cognate decoding, whereas it is dispensable for intrinsic GTPase activity (42). It was suggested that basal GTP hydrolysis of trGTPases does not involve side chains of Asp21 and His84.…”
Section: A2662 Thiophosphate Diastereomers Both Have Wt Activities Inmentioning
confidence: 99%
“…His84 in the switch II is conserved in all trGTPases. Mutation of His84 to alanine (His84Ala) completely abolishes the acceleration of GTP hydrolysis by the ribosome . Due to the neutral pK a of histidine in solution and its position close to the catalytic water molecule, as seen from the structure of the ribosome‐bound EF‐Tu in the pre‐hydrolysis state (Figure b), His84 was proposed to act as a general base .…”
Section: Multiple Pathways Of Gtp Hydrolysismentioning
confidence: 99%